Correction: Nanomolar LL-37 induces permeability of a biomimetic mitochondrial membrane. Issue 48 (1st December 2022) - Jiang, Xin; Yang, Chenguang; Qiu, Jie; Ma, Dongfei; Xu, Cheng; Hu, Shuxin; Han, Weijing; Yuan, Bing; Lu, Ying
Abstract : Correction for 'Nanomolar LL-37 induces permeability of a biomimetic mitochondrial membrane' by Xin Jiang et al., Nanoscale, 2022, ; https://doi.org/10.1039/d2nr05409d .